Reconciling Competing Globalizations through Regionalisms? Environmental Security in the Framework of Expanding Security Norms and Narrowing Security Policies. Issue 6 (1st November 2016) - Koff, Harlan
Abstract: This article examines environmental security regimes in 16 regional organizations and asks whether regions can effectively implement environmental security norms. It first defines these norms and discusses their emergence at the international level. At the same time, through the literature review, the article posits that the globalization of security threats has simultaneously led to a retrenchment of coercive non-state security strategies. Consequently, the article contends that the globalization of security norms has made them ineffectual because they have not properly addressed tangible security threats. At the same time, nation-state-based hard power security measures (especially border controls) have not adequately addressed the underlying causes of transnational threats related to human and environmental security. For this reason, the article examines how well regional approaches to security contribute to both protection against imminent violence and the promotion of human and environmental security through medium-term development strategies. The article contends that the emergence of regional environmental security regimes should be fostered by reinforcing regional security architectures through public participation mechanisms.